Functional and Traditional Resistance Training Are Equally Effective in Increasing Upper and Lower Limb Muscular Endurance and Performance Variables in Untrained Young Men - Zuo, Chongwen; Bo, Shumin; Wang, Tao; Zhang, Wei (Frontiers in Physiology, 2022)
Background: Functional resistance training (FRT) has been proposed as a safe alterna-tive to traditional resistance training (TRT) for developing neuromuscular adaptation capacity and improving muscular strength and competitive performance. This study sought to compare the effects of six weeks of FRT and TRT on upper and lower limb muscular endurance and performance variables in untrained young men. Methods: Twenty-nine untrained healthy young males aged 18–29 years were randomly given six weeks of FRT [40% of 1repetition maximum (RM), 4–5 sets of 20 repetitions, 3 times/week] or TRT (70% of 1RM, 4–5 sets of 12 repetitions, 3 times/week). All partici-pants underwent numerous tests before and after the six-week training, such as mus-cular endurance (reps of bench press and leg flexion) and physical performance tests (sprint performance, pull-ups, throwing ability, and jumping ability). Results: After the six weeks of training, the TRT and FRT groups showed an equally significant increase in muscular endurance (p < 0.01), while the throwing and jumping abilities, 30-m sprint, and pull-ups performances in both the groups (p < 0.01) also im-proved significantly. However, no differences were observed between the groups (p > 0.05). Conclusion: These findings indicate that both functional resistance training and tradi-tional resistance training are effective training methods for improving the upper and lower limb muscular endurance and performance in untrained young men.